Development and validation of two competitive ELISAs for detecting human and canine adenovirus antibody in Ontario wildlife sera. - Maxwell, Laura. (University of Ottawa (Canada), 2000)
A human adenovirus type 5-rabies recombinant vaccine(Ad5RG) is a potential candidate for the oral immunization of skunks, foxes, and raccoons against rabies. Adenovirus seroprevalence studies in these species were required before using the vaccine in the field, as part of an environmental risk assessment and for determining if a barrier to immunization exists. For this purpose, two competitive enzyme-linked immunosorbent assays (cELISAs) measuring antibodies (Ab) against Ad5 and canine adenovirus type one (CAV-1) were developed and validated. Sera were examined for either Ad5 or CAV-1 neutralizing antibodies using plaque reduction neutralization tests (PRNT). The Ad5 cELISA was 80% sensitive and 75% specific when an 8% inhibition positivity cutoff was, used. The CAV-1 cELISA was 83% sensitive and 96% specific when a 17% inhibition positivity cut off was used. Contributing to the low Ad5 specificity in particular were raccoons that generally lacked Ad5 neutralizing activity but had Ab which bound purified Ad5 in the cELISA and Western blot. (Abstract shortened by UMI.)
Keywords: Health Sciences, Immunology.